2022
DOI: 10.1177/09610006221111199
|View full text |Cite
|
Sign up to set email alerts
|

Librarians self-efficacy in ICT-based library operations and services: A survey of librarians working in libraries of Aligarh Muslim University Library System

Abstract: This study aimed to determine the level of ICT self-efficacy among librarians working in the Libraries of Aligarh Muslim University Library System (AMULS). A structured questionnaire was used to conduct a quantitative survey. One of the researchers visited the Maulana Azad Library, Faculty and College Libraries, Departmental and Seminar Libraries, and School Libraries and distributed the questionnaire to librarians. On the other hand, librarians of the AMU regional centers’ libraries were contacted through ema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The reliability of the questionnaire was authenticated by reliability analysis using SPSS version 23 with subscales.Cronbach's alpha is a metric used to assess the consistency of a set of scales, such as "level of digital literacy" (=.839) and "attitude toward blended mode of learning" (=.932). However, the values for Cronbach's alpha of 0.7 to 0.10 are considered highly acceptable, as suggested in the earlier study by Nazim, et al 27 Table 1 shows the demographic characteristics of the respondents. The analysed data shows that more than seventy percent of the respondents were male (n= 211, 72.5 %) while only 27.5 % of them were female.…”
Section: Methodsmentioning
confidence: 81%
“…The reliability of the questionnaire was authenticated by reliability analysis using SPSS version 23 with subscales.Cronbach's alpha is a metric used to assess the consistency of a set of scales, such as "level of digital literacy" (=.839) and "attitude toward blended mode of learning" (=.932). However, the values for Cronbach's alpha of 0.7 to 0.10 are considered highly acceptable, as suggested in the earlier study by Nazim, et al 27 Table 1 shows the demographic characteristics of the respondents. The analysed data shows that more than seventy percent of the respondents were male (n= 211, 72.5 %) while only 27.5 % of them were female.…”
Section: Methodsmentioning
confidence: 81%
“…However, many scholars' emphasis that to satisfy user demands, academic libraries have introduced a variety of digital services, such as email services, online consultations, chat services, digital preservation, cybersecurity, etc. (Okeji et al, 2020;Nazim et al, 2023). As Mazumdar (2007) highlighted that "since the technology revolution has given rise to various breakthroughs and inventive concepts, librarians need to become lifelong learners" (p. 423).…”
Section: Emerging Technological Competenciesmentioning
confidence: 99%
“…Notably, many librarians have moderate and low levels of skills in digitization, digital library development, adopting emerging technologies into library services, and maintaining library websites. Nazim et al (2023) revealed that a large number of LIS professionals have positive attitudes towards the impact of ICT applications on library management and services. However, they identified that the professionals are competent in managing electronic information, applying network and security systems, using web OPAC, database management, and marketing information through social media platforms, etc.…”
Section: Emerging Technological Competenciesmentioning
confidence: 99%
“…Schunk and Usher (2011) defined self-efficacy as assessing the individuals’ beliefs in their capability to perform a task successfully. In the case of library professionals, self-efficacy regarding online information retrieval relates to their confidence and proficiency in effectively using electronic and digital resources to provide the assistance to library patrons in their information searching and retrieving endeavors (Nazim et al , 2023). Mastery experience, vicarious experience, social persuasion and physiological states collectively contribute to the development of library professionals’ self-efficacy (Alshahrani and Rasmussen Pennington, 2020).…”
Section: Introductionmentioning
confidence: 99%